Using of Hypercorrection in Diagnostics and Functional Treatment of Children with Strabismus - S. I. Rychkova; V. G. Likhvantseva (Oftalʹmologiâ, 2020)
Conjunctival lymphomas are predominantly extranodal B-cell non-Hodgkin’s lymphomas (NHL), most of them are MALT-lymphomas originating from the mucosa-associated lymphoid tissue. The paper is devoted to the study of the feasibility of using hypercorrection in the functional treatment of children with non-paralytic strabismus.The purpose of this work is evaluation of the effectiveness of hypercorrection in the diagnosis and functional treatment of children with non-paralytic strabismus. Patients and methods. We observed 166 school-age children with friendly strabismus: 140 children with esotropia (134 children with hypermetropic refraction and 6 children with myopic refraction) and 26 children with exotropia (17 children with myopic refraction and 9 children with hypermetropic refraction). The control group of children included 151 school-age children with ametropia without strabismus: 110 children with hypermetropia and 41 children with myopia. Optimal optical correction, accommodation and visual acuity were studied under monocular observation conditions and then under bifixation control using a binarimeter at different distances from the eyes (0.5, 1, and 5 m).Results. In children with esotropia and hypermetropic refraction, the most favorable conditions for the formation of a binocular visual image (BVI) were created using hypercorrection (average values from 2.4 ± 0.06 to 2.8 ± 0.06 D for different distances from the eyes). Children with exotropia and myopic refraction also needed hypercorrection to form BVI (Me = 2.5 [Q1 = 2.0; Q3 = 3.0] D at all distances from the eyes). At the same time, a strong positive correlation was found between the deviation value and the hypercorrection value necessary for the formation of BVI in children with both esotropia and exotropua (r = 0.85, p < 0.001 and r = 0.8, p < 0.001, respectively). In children with “inappropriate” refraction (myopic with esotropia and hypermetropic — with exotropia), BVI was easier to occur and better maintained under hypocorrection by an average of 1.75 ± 0.06 d. In the control group of children, the maximum visual acuity under the control of BVI was observed with the strength of correcting lenses 0.5 D less compared to monocular conditions of the study.Conclusion. The effectiveness of using hypercorrection in children with non-paralytic strabismus and “appropriate” refraction for the formation of BVI on a binarimeter is shown. In this case, the value of hypercorrection has a direct dependence on the value of deviation, which is consistent with the principles of accommodation-convergent synkinesia. In children with non-paralytic strabismus and “inappropriate” refraction, more favorable conditions for the formation of BVI are created when using hypocorrection. The result of functional treatment on a binarimeter with an individual selection of optimal optics for performing exercises is an improvement of accommodation, binocular and stereo vision, an increase of fusion reserves and visual acuity.